2022
DOI: 10.54518/rh.2.1.2022.283-294
|View full text |Cite
|
Sign up to set email alerts
|

Improving Regional Financial Management through Administration of Regional Property and Financial Reporting on Regional Assets

Abstract: Local government financial management mechanisms have continued to undergo significant changes in recent years. This article seeks to reveal the process and analysis of academic activities to support the performance of the regional financial and asset management office as a form of assistance and understanding of regional financial and asset management as a form of knowledge. This activity was carried out at the Regional Financial and Asset Management Agency of Central Sulawesi Province, starting with the prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In this system, the recording of economic transactions is done by recording singly (not in pairs). Transactions that increase cash will be recorded on the Receiving side, and transactions that result in a decrease in cash will be on the Expenditure side (Pattawe et al, 2022). This recording has been practised in the Regional Government for almost three decades.…”
Section: Overview Of Regional Financementioning
confidence: 99%
“…In this system, the recording of economic transactions is done by recording singly (not in pairs). Transactions that increase cash will be recorded on the Receiving side, and transactions that result in a decrease in cash will be on the Expenditure side (Pattawe et al, 2022). This recording has been practised in the Regional Government for almost three decades.…”
Section: Overview Of Regional Financementioning
confidence: 99%
“…Research in Indonesia found that the use of information technology has a positive effect on the quality of local government financial reports (Rahman & Fachri, 2016;Yuliani & Agustini, 2016). Proper use of information technology by organizational units to identify, process transaction data, and generate information electronically increases the reliability and timeliness of financial reports (Din, Paranoan, Azdar, & Ralis, 2022;Jauhari, Sari, & Dewata, 2019;Pattawe et al, 2022). The extensive use of technology makes it possible to increase the accountability of local financial management processes.…”
Section: Local Governmentsmentioning
confidence: 99%
“…The government is making efforts to increase the pace of economic development, which is expected to accelerate over time. One of them is by implementing the development of the financial sector, which is expected to grow rapidly (Madura, 2020;Pattawe et al, 2022). However, over time, monetary developments even had the opposite impact, causing the relationship between economic growth, the money supply, and the inflation rate to be shaken, resulting in a monetary crisis and destroying parts of the economy.…”
Section: Figure 1 Graph Of Inflation Rate In Indonesiamentioning
confidence: 99%